Preparation and evaluation of injectable dosage form for Pemetrexed-monoclonal antibody conjugate - Faten Q. Ibraheem; Nidhal K. Maraie; Basma Talib Al-Sudani (Iraqi Journal of Pharmaceutical Sciences, 2025)
Antibody-drug conjugates (ADCs), a powerful type of pharmaceutical medications that combine immunotherapy and chemotherapy. Pemetrexed is a multitarget antifolate agent that inhibit essential enzymes involve in purine and pyrimidine synthesis, therefore serious toxicities of pemetrexed are due to lack of selectivity despite its broad antitumor activity in a wide variety of solid tumors. The aim of the study was to formulate and evaluate our prepared Atezolizumab (AtZ)-pemetrexed (Pem) conjugates as an intravenous (I.V) injectable dosage form. The characterization of the I.V formulation involved drug content, particle size, pyrogen test, sterility test, toxicity test, and stability test. The work revealed that our previously prepared AtZ-Pem conjugate products (both using PEG and gamma amino butyric acid GABA as linkers) showed different retention time by HPLC-UV, the particle size of the I.V dosage form revealed that AtZ-GABA-Pem had smaller size (465nm) and more uniform size distribution (PDI 0.451), while the particle size and PDI for AtZ-PEG-Pem were (1297nm) and (0.9912) respectively. The two prepared I.V preparations for AtZ-PEG-Pem and AtZ-GABA-Pem showed good stability after six months storage at 6 °C, unacceptable stability results when both formulas stored at room temperature. Both I.V preparations for the conjugates were not toxic, sterile, and pyrogen free. The prepared injectable preparation could be used as a potential alternative to the available injectable preparations for Pemetrexed to improve its targeting and selectivity, hence reducing its serious side effects.